Morphometric evaluation of keratocystic odontogenic tumor before and after marsupialization - Deborah Campos Telles; Wagner Henriques Castro; Ricardo Santiago Gomez; Giovanna Ribeiro Souto; Ricardo Alves Mesquita (Sociedade Brasileira de Pesquisa Odontológica, 2013)
The aim of the present study was the morphometric evaluation of the epithelial lining and fibrous capsule in histological specimens of keratocystic odontogenic tumors (KOTs) before and after marsupialization. Histological sections from six KOTs that had undergone marsupialization followed by enucleation were photographed. The thickness and features of the capsule and of the epithelial lining of the tumor were evaluated upon marsupialization and upon subsequent enucleation using Axion Vision software. The histological specimens taken upon marsupialization presented an epithelial lining that is typical of KOTs. After marsupialization, the enucleated specimens had a modified epithelial lining and a fibrous capsule that both presented a greater median thickness (p = 0.0277 and p = 0.0212, respectively), morphological changes, and significant enlargement. These modifications can facilitate full surgical treatment and may well be related to a low KOT recurrence rate.